Technology Use and Integration in Adult Education and Literacy Classrooms - Glenda Lynn Rose; Chih-Wei Wang; Amanda Sainz; Suresh Joshi (Adult Education Research Conference, 2019)
Instructors and programs in adult education and literacy classrooms face challenges with technology integration due to minimal internet and mobile phone service availability, and limited financial support for professional development.
Keywords: Technology integration; Adult education and literacy; AEL instructor